Celebrating power in everyday life: the administration of law and the public sphere in colonial Tanzania, 1890-1914 - Deutsch, J (Carfax Publishing, 2002)
The paper examines the way in which power was routinely exercised in colonial German East Africa in everyday life. In order to achieve domination rather than ruling just by brute force, the German administration set up district councils called Schauri, in which members of the local African élite were invited to act as advisors to the District Officer. The highly formalized meetings of the council were held in public at least once a week. The district officer had the final say in all matters. The council members deliberated the most mundane aspects of colonial rule. Yet the meetings also dealt with more substantive issues, such as the administration of law in the district, local political affairs or the latest public decree from the Governor in Dar es Salaam. The paper argues that the Schauri meetings constituted the most important field of political interaciton and engagement between the German rulers and their African subjects. These meetings were thus an indispensible part of what one might call the 'colonial public sphere'.